Limb-Bone Development of Seymouriamorphs: Implications for the Evolution of Growth Strategy in Stem Amniotes - Estefa, Jordi; Klembara, Jozef; Tafforeau, Paul; Sanchez, Sophie (Frontiers in Earth Science, 2020)
Tetrapod life on land was the result of a lengthy process, the final steps of which resulted in full independence of amniotic tetrapods from the aquatic environment. Developmental strategies, including growth rate and the attainment of sexual maturity, played a major role in this transition. Early amniotes, such as Ophiacodon, tended to reach sexual maturity in a year while most non-amniotic Paleozoic tetrapods (including Devonian tetrapods and temnospondyls) became adult after 3 to 11 years. This ontogenetic transition is accompanied by a drastic change in growth rate and bone microstructure suggesting faster growth dynamics in early amniotes than in Devonian tetrapods and temnospondyls. Was the acquisition of a faster development (earlier sexual maturity and faster growth rate) a drastic evolutionary event or an extended process over geological time? To answer this question, the limb bone histology of two Early Permian (i.e. 270-290 million-year-old) stem-amniote seymouriamorphs, Seymouria sanjuanensis and Discosauriscus austriacus, were investigated. We used three-dimensional bone paleohistology based on propagation phase-contrast synchrotron microtomography. Both seymouriamorphs display relatively fast bone growth and dynamics (even though cyclic in the humerus of D. austriacus). This significantly contrasts with the slow primary bone deposition encountered in the stylopods of temnospondyls and Devonian (i.e. 360 million-year-old) stem tetrapods of similar sizes. On the basis of skeletochronological data, the seymouriamorph D. austriacus retained a long pre-reproductive period as observed in Devonian tetrapods and most temnospondyls. The combination of characteristics (faster growth rate but long pre-reproductive period) suggests that the shift towards an amniotic developmental strategy was an extended process in the evolutionary history of amniotes.